2016
DOI: 10.1007/s11199-016-0665-3
|View full text |Cite
|
Sign up to set email alerts
|

Not Feeling Good in STEM: Effects of Stereotype Activation and Anticipated Affect on Women’s Career Aspirations

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 58 publications
9
49
1
6
Order By: Relevance
“…Our findings support previous research (Mau, 2003;Mau & Bikos, 2000;Schuster & Martiny, 2017) indicating the existence of important factors influencing the STEM career aspirations of female and minority high school students. In particular, this study adds to the understanding of the roles of familial support, school influence, and career self-efficacy in the STEM career decision-making process.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings support previous research (Mau, 2003;Mau & Bikos, 2000;Schuster & Martiny, 2017) indicating the existence of important factors influencing the STEM career aspirations of female and minority high school students. In particular, this study adds to the understanding of the roles of familial support, school influence, and career self-efficacy in the STEM career decision-making process.…”
Section: Resultssupporting
confidence: 92%
“…In line with previous studies (Howard et al, 2011;Mau, 2003;Mau & Bikos, 2000;Padilla-Carmona & Martínez-García, 2013;Riegle-Crumb, Moore, & Ramos-Wada, 2011), gender and race were salient predictors of high school students' career aspirations and, as might be expected, remained strong predictors of STEM aspirations when all familial/parental, school/academic, and personal/psychological variables were taken into consideration. As with many prior studies (Belser, Prescod, Daire, Dagley, & Young, 2017;Fouad et al, 2010;Gnilka & Novakovic, 2017;Haynes & Jacobson, 2015;Raque-Bogdan et al, 2013; Schuster & Martiny, 2017), the female and minority students in our study experienced several barriers, such as lack of confidence, unfair treatment, discrimination, financial pressure, stereotypes, and biases, which help explain their lack of interest in STEM careers. Because female and minority students encounter many barriers in their educational and vocational pursuits, counselors working in school and other contexts should provide system-wide supports that increase female and minority academic, career, and personal/social success.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Many career options may not be considered simply because they were unaware of these opportunities because job placement advertisements are not targeting women (Glass and Minnotte 2010;McNeely and Vlaicu 2010). Even when students are aware of career options, they may not seriously consider those options because women have inaccurate information regarding either the option itself, are undecided about their career plans, or they doubt their ability to achieve in that field (Schuster and Martiny 2016). Xu (2017) found that strong academic performance in major-related courses contributed to the increased likelihood of students working in STEM-related fields.…”
Section: Careersmentioning
confidence: 99%
“…Female representation at conferences and in the workplace consistently leads to increased female participation in science (Murphy et al 2007;Young et al 2013;Miller et al 2015;Sardelis and Drew 2016). Conversely, exposure to gender stereotypes decreases women's self-esteem (Sanchez and Crocker 2005) and job success (Reuben et al 2014;Schuster and Martiny 2017), and can result in depression (Sanchez and Crocker 2005;Panayiotou and Papageorgiou 2007). As early as six, girls are less likely to believe that members of their own gender can be considered "really, really smart" when compared with the boys in their class and will even begin to avoid activities that they associate with intelligence (Bian et al 2017, p. 389).…”
Section: Loverock and Hartmentioning
confidence: 99%